Interpretation of the Qur'anic Managerial Commentary on Caliphate, ‘Ibad, and Amanah in the Context of Human Responsibility - Mujadid, Shofam Amim; Mahmud, Hamidullah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
The ongoing leadership crisis, low integrity, and weak organizational governance highlight the need for a managerial paradigm grounded not only in technical competence but also in moral and spiritual values. This article aims to reconstruct the Qur’anic concept of human responsibility by integrating three key notions—khalifah (leadership mandate), ‘ibad (servanthood and value orientation), and amanah (trust and accountability)—into the framework of Qur’anic Managerial Responsibility (QMR). The study employs a qualitative approach using thematic (maudhu‘i) interpretation and hermeneutical analysis, examined through the lens of contemporary Islamic management theory. Data are derived from Qur’anic verses, classical and modern tafsir literature, and scholarly works on Islamic leadership and management. The findings demonstrate that khalifah represents a strategic leadership mandate and sustainable stewardship, ‘ibad constitutes the spiritual–ethical foundation guiding leadership behavior, and amanah functions as a structure of moral and institutional accountability. The integration of these three pillars forms a holistic Qur’anic leadership model conceptualized as Leader–Servant–Trustee. Furthermore, the study shows that QMR is not merely theoretical but can be operationalized in Islamic finance, education, and business sectors through ethical governance and accountability practices. Theoretically, this research bridges the epistemological gap between Qur’anic exegesis and Islamic management studies, offering a value-based leadership framework relevant to contemporary organizational contexts.